COMMUNITY BASED TOURISM AND VOLUNTOURISM ENHANCEMENT FOR KAMPUNG WISATA CISANGKAL IN PANGANDARAN - Kurniawati, Linda; Thirafi, Luthfi; Sitio, Nurul Mardhiah (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2023)
Bangunkarya Village, which is located in Langkaplancar District, Pangandaran Regency, is a village that has natural tourism potential, including durian gardens, coffee plantations, rivers for hanging out together, and several saungs named Cisangkal Tourism Village. When compared to the surrounding villages, namely Selasari and Cintaratu, information regarding tourism potential, location access, umkm, and village facilities is very difficult to find. This is due to the lack of education about the management of tourism facilities to the village community. Aiming to provide education about the management of a tourist village and its benefits for the village economy, the community service team held a workshop related to a tourism village for residents in Bangunkarya Village. The results of the workshop show that the people of Bangunkarya Village have little access to information about managing a tourism village, while village officials still don't have the desire to build a community-based tourism village.